2023
DOI: 10.15789/1563-0625-aom-2630
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of maximal SARS-CoV-2 collective immunity among the Tajik population by March 2022

Abstract: Despite all efforts of the world community, the COVID-19 pandemic remains one of the main epidemiological challenges of our time. Even with its widespread distribution, the infection may have certain local features due to social, geographic, and climatic factors. Objective: to study collective immunity to SARS-CoV-2 in the population of the Republic of Tajikistan.A cross-sectional, randomized study of herd immunity was carried out according to a program developed by Rospotrebnadzor and the St. Petersburg Paste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The current pandemic has shown that a characteristic feature of COVID-19 is a large number of asymptomatic forms. The manifestations of this Moreover, the highest rates of asymptomatic cases in all countries were noted among children [5,6,7,10,11,12,14].…”
Section: закономерности коллективного иммунитета к Covid-19mentioning
confidence: 90%
See 3 more Smart Citations
“…The current pandemic has shown that a characteristic feature of COVID-19 is a large number of asymptomatic forms. The manifestations of this Moreover, the highest rates of asymptomatic cases in all countries were noted among children [5,6,7,10,11,12,14].…”
Section: закономерности коллективного иммунитета к Covid-19mentioning
confidence: 90%
“…It was implemented in 2020-2021 in Russia [5,7,14]. Since 2021-2023, neighboring countries have participated in a partnership program (Armenia, Belarus, Kyrgyzstan, Tajikistan) [6,10,11,12]. The program has included the formation of volunteer cohorts, the volume and structure of which has made it possible to obtain representative data for the populations in the study region (countries) by age and professional group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations